Comparison of ACUITY and CRUSADE Scores in Predicting Major Bleeding during Acute Coronary Syndrome - Luis C. L. Correia; Felipe Ferreira; Felipe Kalil; André Silva; Luisa Pereira; Manuela Carvalhal; Maurício Cerqueira; Fernanda Lopes; Nicole de Sá; Márcia Noya-Rabelo (Arquivos Brasileiros de Cardiologia, 2015)
Background: The ACUITY and CRUSADE scores are validated models for prediction of major bleeding events in acute coronary syndrome (ACS). However, the comparative performances of these scores are not known. Objective: To compare the accuracy of ACUITY and CRUSADE in predicting major bleeding events during ACS. Methods: This study included 519 patients consecutively admitted for unstable angina, non-ST-elevation or ST-elevation myocardial infarction. The scores were calculated based on admission data. We considered major bleeding events during hospitalization and not related to cardiac surgery, according to the Bleeding Academic Research Consortium (BARC) criteria (type 3 or 5: hemodynamic instability, need for transfusion, drop in hemoglobin ≥ 3 g, and intracranial, intraocular or fatal bleeding). Results: Major bleeding was observed in 31 patients (23 caused by femoral puncture, 5 digestive, 3 in other sites), an incidence of 6%. While both scores were associated with bleeding, ACUITY demonstrated better C-statistics (0.73, 95% CI = 0.63 - 0.82) as compared with CRUSADE (0.62, 95% CI = 0.53 - 0.71; p = 0.04). The best performance of ACUITY was also reflected by a net reclassification improvement of + 0.19 (p = 0.02) over CRUSADE’s definition of low or high risk. Exploratory analysis suggested that the presence of the variables ‘age’ and ‘type of ACS’ in ACUITY was the main reason for its superiority. Conclusion: The ACUITY Score is a better predictor of major bleeding when compared with the CRUSADE Score in patients hospitalized for ACS.